The Role of Credit Markets in a Transition Economy with Incomplete Public Information - Roldos, Jorge (IMF Working Papers; Working Paper ;, 1996)
In this paper we explore some of the informational problems that constrain the development of credit markets in transition economies. We characterize investment patterns under uncertainty and high costs of entry, when agents learn about the ultimate value of enterprises through production in a Bayesian way. Inefficiencies due to the lack of public information reduce the average return to capital. Under asymmetric information, credit would go to activities that can provide enough co-finance. Credit markets may fail to develop for a while if there is not enough individual wealth to complement credit. Once they operate, credit markets may magnify distortions in equity markets, such as those due to spontaneous privatization. An argument for the sequencing of capital market liberalization is provided.